Penatalaksanaan Fisioterapi Kombinasi SWD, TENS, dan Terapi Latihan pada Frozen Shoulder Dextra Lansia: Studi Kasus - Rizki Aulia Sari; Rosella Komalasari; Munawar Munawar (Journal of Educational Innovation and Public Health, 2026)
Frozen  shoulder or adhesive capsulitis is a chronic condition that causes pain and limited movement in the shoulder joint. Intervention in the early phase (freezing stage) is crucial to prevent more severe functional disabilities, especially in the elderly population. This case study was conducted on a 60-year-old female patient with complaints of pain and stiffness in the right shoulder for one month. Clinical assessment was conducted using the Numeric Rating Scale (NRS) for pain, Manual Muscle Testing (MMT) for muscle strength, goniometry for joint range of motion, and the Shoulder Pain and Disability Index (SPADI) for functional ability. The therapy program was administered in three intervention sessions. After undergoing three therapy sessions, there was a significant reduction in pain intensity, where movement pain decreased from a score of 7 to 5 and pressure pain from 5 to 2. Muscle strength improved from a value of 3 to 4 on the MMT scale. Additionally, the total SPADI score decreased from 66.1% to 50%, indicating an improvement in the patient's functional capacity in daily activities. The multimodal physiotherapy approach has proven effective in reducing pain, increasing muscle strength, and improving shoulder function in elderly patients with early-stage frozen  shoulder. The combination of electro-physical modalities and manual therapy provides more comprehensive clinical outcomes compared to single interventions.